Treatment patterns and outcomes of patients with relapsed or refractory follicular lymphoma receiving three or more lines of systemic therapy (LEO CReWE): a multicentre cohort study. Issue 4 (April 2022) - Casulo, Carla; Larson, Melissa C; Lunde, Julianne J; Habermann, Thomas M; Lossos, Izidore S; Wang, Yucai; Nastoupil, Loretta J; Strouse, Christopher; Chihara, Dai; Martin, Peter; Cohen, Jonathon B; Kahl, Brad S; et al.
Summary: Background: Novel therapies for relapsed or refractory follicular lymphoma are commonly evaluated in single-arm studies without formal comparison with other treatments or historical controls. Consequently, rigorously defined treatment outcomes informing expectations for novel therapeutic strategies in this population are sparse. To inform outcome expectations, we aimed to describe treatment patterns, survival outcomes, and duration of response in patients with relapsed or refractory follicular lymphoma receiving three or more lines of systemic therapy. Methods: In this multicentre cohort study, we developed a database of patients with relapsed or refractory follicular lymphoma from eight academic centres in the USA using data collected in the LEO Cohort study (NCT02736357 ) and the LEO Consortium. For this analysis, eligible patients were aged at least 18 years, had non-transformed grade 1–3a follicular lymphoma, and were receiving systemic therapy in the third line or later after previous therapy with an anti-CD20 antibody and an alkylating agent. Clinical data and patient outcomes were abstracted from medical records by use of a standard protocol. The index therapy for the primary analysis was defined as the first line of systemic therapy after the patient had received at least two previous systemic therapies that included an alkylating agent and an anti-CD20 therapy. The main endpoints of interest were overall response rate, progression-free survival, and overall survival. Outcomes were also evaluated in subsets of clinical interest (index therapy characteristics, patient and disease characteristics, treatment history, and best response assessment). Findings: We screened 933 patients with follicular lymphoma, of whom 441 were included and diagnosed between March 6, 2002, and July 20, 2018. Index therapies included immunochemotherapy (n=133), anti-CD20 antibody monotherapy (n=53), lenalidomide with or without anti-CD20 (n=37), and phosphoinositide 3-kinase inhibitors with or without anti-CD20 (n=25). 57 (13%) of 441 patients received haematopoietic stem-cell transplantation and 98 (23%) of 421 patients with complete data received therapy on clinical trials. After a median follow-up of 71 months (IQR 64–79) from index therapy, 5-year overall survival was 75% (95% CI 70–79), median progression-free survival was 17 months (15–19), and the overall response rate was 70% (65–74; 280 of 400 patients evaluable for response). Patients who were refractory to therapy with an alkylating agent had a lower overall response rate (170 [68%] of 251 patients vs 107 [77%] of 139 patients) and a significantly lower 5-year overall survival (72%, 95% CI 66–78 vs 81%, 73–89; hazard ratio 1·60, 95% CI 1·04–2·46) than patients who were not refractory to therapy with an alkylating agent. Interpretation: Patients with relapsed or refractory follicular lymphoma receive heterogeneous treatments in the third-line setting or later. We observed high response rates to contemporary therapies that were of short duration. These data identify unmet needs among patients with follicular lymphoma, especially those who are refractory to alkylating agents, and might provide evidence by which clinical trials evaluating novel treatments could be assessed. Funding: Genentech and the National Cancer Institute.